2011
DOI: 10.1097/sla.0b013e318216f374
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variants in DNA Repair Predicts the Survival of Patients with Esophageal Cancer

Abstract: Genetic variants in ERCC2 and ERCC4 may provide further survival prediction in addition to TNM staging system of esophageal cancer, which is more evident in the patients with early disease status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 48 publications
2
6
1
Order By: Relevance
“…While five of these SNPs were not associated with progression-free survival among HNC cases, four SNPs appeared to be associated with worse progression-free survival contrary to our study [10, 16]. Among esophageal cancer cases, a study by Lee et al [41] did assess rs3136038 reporting better overall survival associated with the genotype TT, though HRs were not statistically significant, similar to our study. Further, ERCC4 protein expression has been found to be elevated in HNC cell lines and displayed cisplatin resistance [42].…”
Section: Discussionsupporting
confidence: 58%
“…While five of these SNPs were not associated with progression-free survival among HNC cases, four SNPs appeared to be associated with worse progression-free survival contrary to our study [10, 16]. Among esophageal cancer cases, a study by Lee et al [41] did assess rs3136038 reporting better overall survival associated with the genotype TT, though HRs were not statistically significant, similar to our study. Further, ERCC4 protein expression has been found to be elevated in HNC cell lines and displayed cisplatin resistance [42].…”
Section: Discussionsupporting
confidence: 58%
“…In the present study, we found that the ERCC2 / XPD rs238406 TT genotype was associated with a reduced DFS and OS in ESCC patients, but few studies have reported its role in prognosis of cancer patients. One Taiwan study found that ERCC2 / XPD rs238406 CC (or GG of its antisense) instead of the AA (or TT of its antisense) genotype of 185 ESCC patients with neoadjuvant chemoirradiation followed by esophagectomy could additively increase risk of death and disease progression in cisplatin-based neoadjuvant concurrent chemoradiation therapy [ 34 ]. Contrary to their results, the TT genotype was associated with the worse DFS and OS in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Development of better preventive approaches and more effective treatment modalities requires in-depth understanding of molecular mechanisms involved in the complex process of esophageal carcinogenesis. There is an urgent need for identification of novel molecular markers to provide the clinician with useful information concerning patient prognosis and possible therapeutic options [20-22]. In search of molecular markers our laboratory analyzed global gene expression profiles of ESCCs using commercially available 19.1k cDNA microarrays [23].…”
Section: Introductionmentioning
confidence: 99%